(untitled) (Homoeopathy for All, 2025)
The science of Homeopathy is beyond the contemporary sciences. As mentioned by Dr. Stuart Close in his philosophy, “By mechanical dilution and potentiation poisons may be deprived of their lethal qualities and transformed into healing remedies normally assimilable by the sick organism”. This involves using ultra-diluted substances to stimulate the body during illness. He discussed concepts from Physics, Biology, and Mathematics, such as the Theory of Infinitesimals, Electromagnetic Induction, and Ionisation, etc